Downlink processing algorithms for multi-antenna wireless communications. - Dakdouki, Ali S.
The recent development of communication theory and radio technology has intensified interest in multi-antenna systems as an effective technique to combat fading of the desired signal, tackle interference from other signals, and increase the data rate in wireless communications. This article provides a survey of downlink processing algorithms for multi-antenna systems. The understanding of fundamental downlink processing strategies is extremely important in analyzing the future of high-capacity/high-quality wireless communications.
Keywords: FDD; MIMO system; TDD; Base station; Downlink processing algorithm; Frequency division duplexing; Interference; Mobile station; Multiantenna wireless communication; Multiple-input multiple-output system; Space-time coding; Time division duplexing